2021
DOI: 10.1371/journal.pone.0256742
|View full text |Cite
|
Sign up to set email alerts
|

Gender imbalance amongst promotion and leadership in academic surgical programs in Canada: A cross-sectional Investigation

Abstract: Background Women are underrepresented at higher levels of promotion or leadership despite the increasing number of women physicians. In surgery, this has been compounded by historical underrepresentation. With a nation-wide focus on the importance of diversity, our aim was to provide a current snapshot of gender representation in Canadian universities. Methods This cross-sectional online website review assessed the current faculty listings for 17 university-affiliated academic surgical training departments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 58 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…That domain refers to the constraints that professional women experience compared with their male counterparts 11 . One consequence of these disproportionate constraints is the decreasing numbers of women in leadership roles, particularly as academic rank proceeds 34 . The distinct lack of gender diversity in leadership continues to propagate the power gap between male and female surgeons and leads to a "persistent opportunity gap between the genders."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That domain refers to the constraints that professional women experience compared with their male counterparts 11 . One consequence of these disproportionate constraints is the decreasing numbers of women in leadership roles, particularly as academic rank proceeds 34 . The distinct lack of gender diversity in leadership continues to propagate the power gap between male and female surgeons and leads to a "persistent opportunity gap between the genders."…”
Section: Discussionmentioning
confidence: 99%
“…That domain refers to the constraints that professional women experience compared with their male counterparts 11 . One consequence of these disproportionate constraints is the decreasing numbers of women in leadership roles, particularly as academic rank proceeds 34 . The distinct lack of gender diversity in leadership continues to propagate the power gap between male and female surgeons and leads to a “persistent opportunity gap between the genders.” 34 Previous research has indicated that the difference in the rate of burnout between genders was attenuated when adjusted for academic rank, suggesting that the ability to break the glass ceiling may mitigate burnout 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Across the pond, the General Medical Council Medical School Annual Return found that 52.5% of medical students were female in the 5 medical schools in London, United Kingdom, for the academic year 2017/2018 (2). Despite this, women have lagged behind entering positions that are traditionally dominated by men such as surgery (3) or to take up academic leadership positions, and this phenomenon has persisted for several decades (4). In 2019, 18% of US medical school deans and 19% of clinical department chairs were women (1).…”
mentioning
confidence: 99%